Identification of Victims of Airplane Accident Cases - Robert Hilman Girsang, Asan Petrus (Journal of Medical Care Research and Review, 2022)
Introduction: Indonesia is an archipelagic country consisting of 13,667 islands with an area limit of 2,027,087 km2, has approximately 129 volcanoes, geologically Indonesia is located at the confluence of 4 plates of the world’s plates that are still actively moving, accompanied by 2 series of world volcanoes ( Circum Pacific and Eurosian), whose tail is in Indonesia, causing Indonesia to be in a very unstable geological position. Demographically, Indonesia also consists of various ethnic groups, religions, social backgrounds, cultures, customs and an increasingly dense population (in 2005, 213 million with an annual population increase of 1.3 %), where this situation provides clues that Indonesia is at high risk as a country prone to natural disasters such as earthquakes, tsunamis, landslides, floods and accidents on land, sea and air. Case Report: a case was reported with the victim being a male corpse, the victim was involved in a CASSA 212-200 aircraft crash that occurred on Thursday, September 29, 2011 at Pkl. 07.28 WIT in the Gunung Kapur Forest, Bahorok District, Langkat Regency, North Sumatra Province, Indonesia. Results: external examination found multiple traumas: the face, chest, abdomen and limbs. Examination in found multiple fractures of the skull, ribs, upper arm bone (os.humerus), thighbone (os.femur), lower limbs (os.tibia, os.fibula). it was concluded that the cause of death of the victim was due to the expulsion of brain tissue, torn right and left heart, profuse bleeding accompanied by bruises, abrasions, lacerations, fractures due to blunt force, and the process of decay. Discussion: This case is a case of a mass disaster and the identification of victims of a mass disaster is carried out according to the Disaster Victim Identification (DVI) procedure, based on observations of the trauma experienced by victims in accordance with general accident cases. Conclusion: from external and internal examination, it was concluded that the cause of death of the victim was the expulsion of brain tissue, torn right and left heart, profuse bleeding accompanied by bruises, abrasions, lacerations, fractures due to blunt force trauma. Keywords: blunt trauma, Disaster Victim Identification